The effect of colored or black and white imagery on the cognitive and psychological state of consumers - Ahmed, University Assistant Teacher Muhaned Imad (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2026)
This research examines the impact of colorful marketing campaigns on consumers' psychological processes, comparing them to black and white images. The theory of levels of interpretation utilizes both black and white, stimulating logical thinking. As we know, color has a significant influence on consumers' feelings and emotions. This research concludes that corporate branding is a psychological tool that also affects consumers' memory and decision-making processes. To illustrate this, a case study of the global American company Coca-Cola will be presented.